Prenatal care of Venezuelans in Colombia: migrants navigating the healthcare system - Vanesa Giraldo; Rita Sobczyk; Julián Alfredo Fernández-Niño; Maylen Liseth Rojas-Botero; Ietza Bojorquez (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVES To explore the experiences of irregular (undocumented) Venezuelan migrants in accessing prenatal health services in Colombia and to examine the economic, social, and cultural resources mobilized by them to gain access to care. METHODS Data was retrieved from the qualitative component of a multi-method research conducted with pregnant immigrants in Barranquilla, Colombia, between 2018 and 2019, and triangulated with a review of regulations established by the Ministry of Health and Social Protection. RESULTS Having limited economic capital, participants use social capital from personal networks and migrant organizations. They obtain cultural health capital in the form of information on the health system and use their cultural competencies to interact with this system. CONCLUSIONS FOR PRACTICE Migrants exert their agency through the use of capitals, although with certain constraints. Policies aimed at this social group should consider the strengths of migrants.